Treat-to-target versus dose-adapted statin treatment of cholesterol to reduce cardiovascular risk. (February 2016) - Müller-Wieland, Dirk; Assmann, Gerd; Carmena, Rafael; Davignon, Jean; von Eckardstein, Arnold; Farinaro, Eduardo; Greten, Heiner; Olsson, Anders G; Riesen, Walter F; Shlyakhto, Evgenyi
Clinical guidelines should be based on the best available evidence and are of great importance for patient care and disease prevention. In this respect, the 2013 American College of Cardiology/American Heart Association report is highly appreciated and well-recognized. The report included critical questions concerning hypercholesterolaemia, but its translation into a clinical guideline initiated intense debate worldwide because of the recommendation to switch from a treat-to-target approach for low-density-lipoprotein-cholesterol to a statin dose-based strategy.